Design and implementation of L and X-band filters for the NeXtRAD front end - Gouveia, Dominique (Department of Electrical Engineering, 2017)
Microwave filters are required at the RF front end of a research radar called NeXtRAD to suppress out of band transmitted and received signals. NeXtRAD is a multistatic pulse-Doppler radar system, developed at the University of Cape Town (UCT) in collaboration with the University College London (UCL). It has been designed to operate in two frequency bands, designated as L and X-bands. NeXtRAD will be used as a research tool, for the purposes of measuring sea targets and detecting sea clutter. The measured data will be stored in a database, and it will be made freely available to the public for research purposes. A coaxial comb-line filter was designed, manufactured and measured at L-band. The narrow band measurement results showed that the filter was centred at 1300 MHz, with an equal ripple bandwidth of 210 MHz. The filter has a spurious-free window of 2050 MHz at -60 dB, with the first spurious approximately at 2.86 times the operating frequency. The return loss of the filter was 19.52 dB, and the insertion loss at mid-band was 0.14 dB. The measured filter agreed extremely well with the L-band specifications. The X-band iris coupled filter was also designed, manufactured and measured. The narrow band measurement results showed that the filter was centred at 8.5 GHz, with an equal ripple bandwidth of 121 MHz. The spurious-free window of the measured filter at -60 dB was 6.571 GHz, with the first spurious at 1.82 times the operating frequency. The insertion loss of the filter was measured to be 2 dB at mid-band and the return loss of the filter was measured to be 18.58 dB at mid-band. The filters are currently being used at the RF front end of the NeXtRAD system.